2009
DOI: 10.1007/s10546-009-9423-1
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Vegetation Density on Coherent Turbulent Structures within the Canopy Sublayer: A Large-Eddy Simulation Study

Abstract: Terrestrial ecosystems are characterized by a wide range of canopy vegetation density, which is known to affect turbulent transport processes across the canopy-atmosphere interface. In the presence of a dense and horizontally homogeneous canopy, the canopy sublayer has been described as resembling a plane mixing layer. At the other extreme, where the canopy is essentially absent, the canopy sublayer is typically assumed to be similar to a turbulent boundary layer over a rough surface. However, it remains uncle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
45
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 46 publications
6
45
0
Order By: Relevance
“…This structure has been compared to the longitudinal roll vortex observed in field studies (Wilson 1996). The coherent structures within the canopy sublayer (CSL) have been demonstrated to be similar to those found in the ABL in the sense that they also consist of a strong sweep or ejection motion framed between a pair of streamwise vortices (Finnigan and Shaw 2000;Huang et al 2009b). However, the coherent structures represent a greater fraction of the TKE in the canopy sublayer than in the atmospheric surface layer (ASL) (Finnigan and Shaw 2000).…”
Section: Introductionmentioning
confidence: 89%
“…This structure has been compared to the longitudinal roll vortex observed in field studies (Wilson 1996). The coherent structures within the canopy sublayer (CSL) have been demonstrated to be similar to those found in the ABL in the sense that they also consist of a strong sweep or ejection motion framed between a pair of streamwise vortices (Finnigan and Shaw 2000;Huang et al 2009b). However, the coherent structures represent a greater fraction of the TKE in the canopy sublayer than in the atmospheric surface layer (ASL) (Finnigan and Shaw 2000).…”
Section: Introductionmentioning
confidence: 89%
“…Poggi and Katul (2007b) and Ross and Vosper (2005) have shown that the analytical model fails to model the flow pattern on dense canopies on narrow hills. Third, even though turbulence closure models and large eddy simulation models have been used to simulate flow within and above the canopy in numerous published studies, most numerically reproduced canopy flow is confined to idealized cases: either neutral (Ross and Vosper, 2005;Dupont et al, 2008;Ross, 2008) or weakly unstable (Wang, 2010) atmospheric conditions, or flat terrain with a homogeneous and extensive canopy (Huang et al, 2009;Dupont et al, 2010).…”
Section: Xu Et Al: Stably Stratified Canopy Flow In Complex Terrainmentioning
confidence: 99%
“…Patton and Katul (2009) explored the spatial perturbations of the first and second moments of the velocity and pressure fields for flow over a train of gentle hills covered by sparse or dense vegetation represented by uniformly arrayed rods each with a height that is comparable to the hill height. The proper orthogonal decomposition (POD) technique was used by Huang et al (2009) to study the effects of vegetation density on basic flow statistics and large-scale coherent turbulent structures within the canopy sublayer using five different vegetation densities varying from an extremely sparse canopy to an extremely dense canopy. All of the above approaches used large-eddy simulation (LES); unfortunately it is numerically demanding when a more detailed investigation at a plant or even at a branch level is desired.…”
Section: Introductionmentioning
confidence: 99%